The Parametric Evaluation of 24 to 28 Gigahertz Planar Quasi-Yagi Multiple Array Antenna System Design - Mansor, Zuhanis; Rais, Nurul Husna Mohd; Rahim, Mohamad Kamal A. (IEEE International Conference on Smart Instrumentation, Measurement and Applications (ICSIMA ...) (Online), 2023)
At a frequency of 28 gigahertz, an investigation is conducted into the performance of millimetre wave parametric analysis utilizing a planar quasi-Yagi multiple array antenna system. The proposed quasi-Yagi antenna consists of a microstrip feed, three to five directors, a truncated ground plane that acts as a reflector, and a dipole driver. The MIMO arrangement, which consists of two antenna placement, on the edge of the PCB and the bottom of PCB., is likewise the subject of research and investigation. According to the findings, there were three directors utilized in the proposed design in order to achieve both a satisfactory gain and a satisfactory frequency bandwidth. These results included return loss, bandwidth, gain, and gain pattern. A radiation pattern was also given. According to the reflection coefficient, the suggested two-element planar quasi-Yagi antenna performs well with minimal mutual coupling in the frequency range of 24-30 GHz. This is the case because the mutual coupling is kept to a minimum. It is clear that the antenna did a good job across the frequency range of 24.84 to 29.10 GHz.